HUBUNGAN SGPT DAN SGOT DENGAN JUMLAH TROMBOSIT PADA PASIEN DEMAM BERDARAH DENGUE (DBD) DI RSUDP NTB - Mardiana Maya Utari; Herlinawati Herlinawati; Ety Retno Setyowati (Nusantara Hasana Berdikari, 2022)
Dengue virus infection can attack hepatic cells. Hepar produces thrombopoeitin hormone that regulates platelet production. Platelets are produced in the bone marrow, in the liver and kidneys. One of the causes of decreased platelets in patients with Dengue Hemorrhagic Fever (DHF) is due to dengue virus attack liver cells that interfere with the production of platelets. Liver damage also causes the release of transaminase enzymes SGPT and SGOT, resulting in increased enzyme SGPT and SGOT. This study aims to determine the relationship between SGPT and SGOT levels with platelet counts in patients with Dengue Hemorrhagic Fever at RSUDP NTB The research method used is cross sectional and accidental sample as sampling method. This study used 77 samples. The data analysis used is Chi Square.Based on the analysis of Dengue Hemorrhagic Fever (DHF) patients in RSUDP NTB, the average of SGPT is 81,97 U/L, SGOT 71,6 U/L, and trombosit 106.000 mg/dL. Based on results of chi square analysis there is a relationship between SGPT and SGOT levels and trombosit levels in Dengue Hemorrhagic Fever (DHF) patients in RSUDP NTB. The higher the levels of SGPT or SGOT, the lower of platelet counts.